PEMBINAAN KEMANDIRIAN SANTRI DI DAYAH DARUSSA'ADAH COT TAROM KABUPATEN BIREUEN (Pascasarjana Institut Agama Islam Almuslim Aceh, 2024)
The purpose of this study was to examine the Development of Student Independence at Dayah Darussa'adah Cot Tarom, Bireuen Regency. The research method used was descriptive qualitative with an empirical approach to direct field studies. In this case, the results found from the author's research are that the Student Independence Development Program at Dayah Darussa'adah Cot Tarom Baroh is an initiative designed to equip students with the skills and knowledge needed so that they can live independently and contribute positively to society. In the context of Islamic boarding school education, this program aims to develop the potential of students holistically, both in terms of spirituality, intellectuality, and practical skills. Thus, students do not only become memorizers of the Quran and religious knowledge, but also have the ability to face the challenges of life in the modern world. Through this program, students are expected to become agents of change that bring benefits to their surroundings, and are able to live an independent and quality life. Thus, they will be role models for future generations and can contribute to building a better society.